Labour Relations in the Public Service : Manitoba - Woods, H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
In reference with the Manitoba Labour-Management Review Committee, the author deals with the problem of public employment labour relations and the use of the Review Committee as a device to explore a major public policy problem in industrial relations.